The Unconventional Cytoplasmic Sensing Mechanism for Ethanol Chemotaxis in Bacillus subtilis - Payman Tohidifar (American Society for Microbiology, 2020)
ABSTRACT Motile bacteria sense chemical gradients using chemoreceptors, which consist of distinct sensing and signaling domains. The general model is that the sensing domain binds the chemical and the signaling domain induces the tactic response. Here, we investigated the unconventional sensing mechanism for ethanol taxis in Bacillus subtilis. Ethanol and other short-chain alcohols are attractants for B. subtilis. Two chemoreceptors, McpB and HemAT, sense these alcohols. In the case of McpB, the signaling domain directly binds ethanol. We were further able to identify a single amino acid residue, Ala431, on the cytoplasmic signaling domain of McpB that, when mutated to serine, reduces taxis to alcohols. Molecular dynamics simulations suggest that the conversion of Ala431 to serine increases coiled-coil packing within the signaling domain, thereby reducing the ability of ethanol to bind between the helices of the signaling domain. In the case of HemAT, the myoglobin-like sensing domain binds ethanol, likely between the helices encapsulating the heme group. Aside from being sensed by an unconventional mechanism, ethanol also differs from many other chemoattractants because it is not metabolized by B. subtilis and is toxic. We propose that B. subtilis uses ethanol and other short-chain alcohols to locate prey, namely, alcohol-producing microorganisms. IMPORTANCE Ethanol is a chemoattractant for Bacillus subtilis even though it is not metabolized and inhibits growth. B. subtilis likely uses ethanol to find ethanol-fermenting microorganisms to utilize as prey. Two chemoreceptors sense ethanol: HemAT and McpB. HemAT’s myoglobin-like sensing domain directly binds ethanol, but the heme group is not involved. McpB is a transmembrane receptor consisting of an extracellular sensing domain and a cytoplasmic signaling domain. While most attractants bind the extracellular sensing domain, we found that ethanol directly binds between intermonomer helices of the cytoplasmic signaling domain of McpB, using a mechanism akin to those identified in many mammalian ethanol-binding proteins. Our results indicate that the sensory repertoire of chemoreceptors extends beyond the sensing domain and can directly involve the signaling domain.